1989
DOI: 10.1577/1548-8659(1989)118<0296:catfws>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Age-Determination Techniques for White Sturgeon in California

Abstract: We compared growth patterns of clavicles, cleithra, opercles, medial nuchals, dorsal scutes, and pectoral fin ray sections from white sturgeon Acipenser transmontanus in California. The legibility and interpretability of growth patterns, ease of collection and processing, and relative precision of age estimates were evaluated for each structure with data collected on skeletal structures and morphometric measurements of 147 individuals ranging in size from 31 to 224 cm total length. Various methods were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(89 citation statements)
references
References 8 publications
5
83
1
Order By: Relevance
“…Brennan and Cailliet (1989) noted that bands from this fi n ray were consistent with the bands from fi n spines but did not evalu-ate the use of this fin ray as an aging structure. We found that the second marginal fin ray was simple to remove and that sections provided reliable and clear band counts.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Brennan and Cailliet (1989) noted that bands from this fi n ray were consistent with the bands from fi n spines but did not evalu-ate the use of this fin ray as an aging structure. We found that the second marginal fin ray was simple to remove and that sections provided reliable and clear band counts.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, these life history traits, as well as habitat issues, equate to a difficult recovery process. Age estimates of several species of sturgeon in North America have been evaluated by removing and observing the banding patterns of calcified structures, such as the first marginal pectoral-fin ray, otoliths, scutes, opercula, and sphenoids (Brennan and Cailliet, 1989;Nakamoto et al 2 ;Rossiter et al, 1995;Stevenson and Secor, 1999;Hurley et al, 2004;Jackson et al, 2007;Bruch et al, 2009). Although it is not a true spine, the first marginal pectoral-fin ray of sturgeons commonly is called the fin spine, and hereafter it will be referred to as such in this article.…”
Section: A Validated Minimally Deleterious Methods For Aging Sturgeonmentioning
confidence: 99%
See 2 more Smart Citations
“…Modern samples came from ship strike mortalities and collections by commercial fishermen (8-35 cm stretch gill nets) ensuring that no fish were killed for this project. A piece of the pectoral spine near the base was removed and used to determine age by counting annual rings using transmitted light at 40Â magnification (Brennan & Cailliet 1989;Van Eenennaam et al 1996;Stevenson & Secor 1999;Sulak & Randall 2002). All samples were read blind by two experienced readers.…”
Section: Methodsmentioning
confidence: 99%